2009
DOI: 10.1097/id.0b013e3181b4f857
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Prefabricated and Custom-Made Bars Used for Implant-Retained Mandibular Complete Overdentures

Abstract: The prefabricated bar overdentures showed less bone resorption distal to the implants in comparison with the cast bar implant-retained overdentures, Both the gingival index and the plaque index score were significantly higher in the group treated with the cast bar retained overdenture. The prefabricated bar implant-retained overdenture showed low significant reduction in the bone height after 1 year, and a very highly significant reduction after 18 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 22 publications
0
9
0
3
Order By: Relevance
“…In a clinical study prefabricated bars were compared to custom‐made bars used for implant‐retained mandibular complete overdentures . The authors stated that the increase in bone loss recorded (18‐month follow‐up) in the cast bar group was more than in the prefabricated bar group, perhaps attributable to the accuracy in fabrication of the prefabricated bar, where it has a high‐polished surface, precision, and stress‐free properties.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In a clinical study prefabricated bars were compared to custom‐made bars used for implant‐retained mandibular complete overdentures . The authors stated that the increase in bone loss recorded (18‐month follow‐up) in the cast bar group was more than in the prefabricated bar group, perhaps attributable to the accuracy in fabrication of the prefabricated bar, where it has a high‐polished surface, precision, and stress‐free properties.…”
Section: Discussionmentioning
confidence: 99%
“…In a clinical study prefabricated bars were compared to custom-made bars used for implant-retained mandibular complete overdentures. 14 The authors stated that the increase in bone loss recorded (18-month follow-up) in the cast bar group was more than in the prefabricated bar group, perhaps attributable to the accuracy in fabrication of the prefabricated bar, where it has a high-polished surface, precision, and stress-free properties. These results may be attributed to the difference in the amount of load transmitted to the supporting structures by a rigid cast bar unit and a relatively flexible prefabricated bar joint used to retain the mandibular overdentures.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 9 10 It has been proven that the bone resorption for IODs on prefabricated bars is lower in comparison with IODs on cast bars. 11 In contrast, a systematic review demonstrated similar bone loss around implants supporting IODs with different attachment designs. 12 This retrospective study examined the survival and success rates as well as the prevalence of peri-implantitis of IODs retained by 3 different bar designs.…”
Section: Introductionmentioning
confidence: 98%